2017
DOI: 10.1111/ced.13124
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between salivary and serum anti-desmoglein 1 and 3 antibody titres using ELISA and between anti-desmoglein levels and disease severity in pemphigus vulgaris

Abstract: ELISA for anti-desmoglein antibodies (Dsg) is commonly used for diagnosis and assessment of treatment response in pemphigus vulgaris (PV). The present study was conducted to assess the relationship between salivary and serum Dsg1 and Dsg3 levels, and whether salivary Dsg1 and Dsg3 levels correlate with clinical disease severity of oral mucosal lesions in PV. In total 43, patients with PV with predominantly mucosal involvement were recruited. Both serum and salivary samples were collected from the cases, and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The authors explained these data with the loss of integrity in mucosa and the largest transition of antibodies in saliva. The study of De et al perfectly reproduced this finding and the authors perfectly agreed with the explanation concerning higher Dsg1 levels in severe disease [106]. In contrast to the previously discussed research, one Italian study was designed to assess the use of a BIOCHIP approach compared with ELISA in PV [107].…”
Section: Blistering Diseasessupporting
confidence: 64%
“…The authors explained these data with the loss of integrity in mucosa and the largest transition of antibodies in saliva. The study of De et al perfectly reproduced this finding and the authors perfectly agreed with the explanation concerning higher Dsg1 levels in severe disease [106]. In contrast to the previously discussed research, one Italian study was designed to assess the use of a BIOCHIP approach compared with ELISA in PV [107].…”
Section: Blistering Diseasessupporting
confidence: 64%
“…In analysis of sequential serum samples from patients with PV, the anti‐Dsg3 indices showed a correlation with PDAI scores, while in a further study no correlation was found with either PDAI or ABSIS . Among patients with predominantly mucosal PV, there was no correlation between either serum or salivary anti‐Dsg1 or anti‐Dsg3 antibodies and the total objective component of ABSIS; however, serum anti‐Dsg1 antibodies did correlate with cutaneous ABSIS …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Belloni-Fortina A et al reported a relationship between the titer of anti-Dsg3 and the severity of both cutaneous and mucosal lesions, while they have found that anti-Dsg1 titer relates only to the severity of mucosal lesions (17). Moreover, Mortazavi et al and De D et al showed that the degree of skin damages significantly enhanced upon an increase in the anti-Dsg1 concentrations, but they found no significant correlation between anti-Dsg3 antibodies and the severity of oral mucosal lesions (18,19). Abasq et al have reported that in PV patients, the anti-Dsg3 titer is not necessarily linked to the clinical course of mucosal lesions (20).…”
Section: No (%) Of Positive Patientsmentioning
confidence: 99%